Noise and noise law a practitioner's guide - McManus, Francis; McKenzie, Andy (Edinburgh Edinburgh University Press Limited, 2023)
"The book contains an introduction to basic acoustics. Common law nuisance and statutory nuisance are discussed with special reference to noise. The authors then discuss the legal controls over neighbourhood noise, transport noise and noise in the workplace. A chapter is devoted to the role of human rights law in the control of noise. Separate chapters cover noise mapping and the role of planning in control of environmental noise."--
Introduction-- Basic Acoustics and Human Sound Perception-- The Measurement and Assessment of Noise-- Common Law Nuisance-- Statutory Nuisance-- Neighbourhood Noise-- Noise and Human Rights-- Transport Noise-- Noise Mapping-- Planning and Noise-- Noise in the Workplace--Appendix I Chapter summaries and discussion questions-- Index.
Includes bibliographical references and index.
Keywords: Auditory perception; Environmental law -- Great Britain; Noise control -- Law and legislation -- Great Britain; Noise pollution -- Law and legislation -- Great Britain